ACEH LOCAL PARTIES IN THE HISTORY OF REPUBLIC OF INDONESIA - Ali Geno Berutu (State Institute of Islamic Studies (IAIN) Salatiga, 2021)
Aceh local party is a party that was born from the womb of a prolonged conflict in Aceh. The existence of the Aceh Local party is inseparable from the actions of GAM leaders in maintaining their existence in the land of the Veranda of Mecca. On the other hand the Government of the Republic of Indonesia also does not want what happened to the East-East province to occur in the Aceh province, so various efforts were made to maintain the sovereignty of the Unitary State of the Republic of Indonesia. Efforts by the Indonesian government include military and civil emergency operations that have been implemented in Aceh, although these efforts have proven unable to eliminate GAM's influence in Aceh, so that in the end the peace route was adopted with the signing of the Helsinki MoU in 2005 which signaled an end to the armed conflict in Aceh for forever. This research is a legal research using a law in concrete sense suppressor where law functions or is implemented (law in action) or law that is always moving (recht in beweging).